Karl Schröter and His Interest in Polish Mathematical Logic. Based on Unpublished Archival Documents - Besler, Gabriela; Porwolik, Marek (Logic and Logical Philosophy, 2025)
Karl Schröter (1905-1977) worked in the field of mathematical logic and the foundations of mathematics, first at Westphalian Wilhelm University of Münster [Westfälische Wilhelms-Universität Münster], then at the Berlin Humboldt University [Humboldt-Universität zu Berlin]. From today’s perspective, he is considered the most important mathematical logician in the German Democratic Republic. He founded the Logic School in Berlin and developed mathematical logic in that country. Most academics working in East Germany in mathematical logic and the foundations of mathematics were either direct students of Schröter or studied under his intellectual influence. He referred to his Münster’s supervisor, Heinrich Scholz (1884–1956), and representatives of the Polish School of Mathematical Logic as his teachers of mathematical logic. In this article, we present the results of our research on two topics. First, we give  compared to what has been published so far  an extended scientific biography of Schröter and a complete list of his scientific works. Our second aim is to inform the logical community about unknown archival documents confirming Schröter’s interest in the Polish logic (Stanisław Leśniewski, Jan Łukasiewicz, Alfred Tarski and Mordchaj Wajsberg). To accomplish these two tasks, we conducted archival research in the Münster and Berlin archives, performed a preliminary analysis of the collected documents, and compared our findings with existing publications on Schröter. The archival research made it possible to clarify his scientific curriculum vitae. The documents also indicate areas for further, more detailed research, including those concerning Schröter’s connections with the Polish School of Mathematical Logic.